TÜRKÇE ÖĞRETMEN ADAYLARININ ÜSTBİLİŞSEL DİNLEDİĞİNİ ANLAMAYA YÖNELİK FARKINDALIKLARI. - LÜLE MERT, Esra (Electronic Turkish Studies)
Listening is a process in which a verbal input is comprehended and interpreted. It is an action based on understanding where many processes are realized concomitantly and interactively. It requires phases and may be developed through some activities implemented during education and training environments. It is the first learning step of an individual. Listening starts before one is born and lasts lifelong. Metacognitive skills emerges at the early ages, develops slowly and continues to improve at least until the end of adolescence period. In order to improve the metacognition of the students, first and foremost the teachers are required to have metacognitive skills and notions. Therefore it is highly important to determine how much the teachers, who work at the elementary schools where the metacognitive skills may be provided to the students, are aware of their own metacognition. This study is prepared implementing descriptive survey model. In this study, the “Metacognitive Listening Comprehension Awareness Scale” developed by Katrancı (2012) is used as a data collection tool. The validity and reliability of this scale, consisting of 20 clauses, is confirmed. This study was carried out together with 240 students of the Turkish Teaching Department of İnönü University. The data acquired in this study was analysed using SPSS (Statistical Package for Social Sciences) for Windows 22.0 programme. According to the results of the research, the highest metacognitive listening comprehension awareness level is about “while-listening” activity. “Post-listening” came second while the lowest listening activity is found as “Pre-listening”. However, emphasis is laid on pre-listening activities at the Turkish teaching programme. The total metacognitive listening comprehension scores of the students participated in this study regarding their pre-listening, while-listening and post-listening activities have not been found significant in terms of gender variation.